How well do we know species richness in a well‐known continent? Temporal patterns of endemic and widespread species descriptions in the European fauna. Issue 1 (19th July 2012) - Essl, Franz; Rabitsch, Wolfgang; Dullinger, Stefan; Moser, Dietmar; Milasowszky, Norbert; Gillespie, Thomas
Abstract Aim To analyse if the historical species description process in 10 animal groups differed among widespread and endemic species and to evaluate whether our current knowledge about the diversity of these groups is complete. Location Sixty‐nine terrestrial regions (countries, large islands, archipelagos) covering all of Europe. Methods Based on data from the Fauna Europaea project, we reconstructed the description histories of four vertebrate groups (amphibians, fish, mammals, reptiles) and six well‐studied invertebrate groups (butterflies, grasshoppers, ground beetles, snails, spiders, true bugs) living in terrestrial and freshwater environments. We used accelerated failure time models to test for a possible delay of endemic species detection and to provide conservative estimates of the as yet undescribed proportions of the existing diversity. Results Our data set includes 24, 092 species, of which 7202 (30%) are endemic to one Fauna Europaea region. Species descriptions over time follow different trajectories for endemic and widespread species, with endemic species being described 79 years later than widespread ones, on average. Rates of widespread species descriptions have been low throughout the 20th century despite increasing numbers of active taxonomists, and models indicate that only a minor fraction of extant species is unknown (0.4–3%). By contrast, endemic species accumulation curves do not seem to have levelled off yet. Conservative model predictions suggest that up to 19% of the existing endemic diversity still awaits description in some taxonomic groups. Conclusions Our results suggest that even for well‐studied groups in the world's biogeographically best‐known continent, scientific knowledge of species richness is far from complete and is biased towards widespread species. Research and conservation priorities may thus be misdirected, as, for example, regions with high numbers of as yet unrecognized endemics may not be adequately considered when setting conservation priorities. This is particularly problematic as their mostly small populations make endemic species especially vulnerable to human‐induced pressures.